1989
DOI: 10.1037/0278-7393.15.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Lexical and sentence context effects in word recognition.

Abstract: We are grateful to George Kellas and Paula Schwanenflugel for their comments on earlier drafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
6

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 47 publications
7
102
6
Order By: Relevance
“…Additional evidence against word-based priming has been provided by other researchers (e.g., Dopkins et aI., 1992;Foss, 1982;Foss & Speer, 1991;O'Seaghdha, 1989O'Seaghdha, , 1991Simpson, Peterson, Casteel, & Burgess, 1989). In particular, Foss demonstrated that detection ofa phoneme was facilitated in related versus neutral sentence contexts, but this difference was eliminated when the contexts were scrambled, even though the scrambled related context contained two associates preceding the targets and the adjacency of the associates and targets was maintained.…”
Section: Discussionmentioning
confidence: 86%
“…Additional evidence against word-based priming has been provided by other researchers (e.g., Dopkins et aI., 1992;Foss, 1982;Foss & Speer, 1991;O'Seaghdha, 1989O'Seaghdha, , 1991Simpson, Peterson, Casteel, & Burgess, 1989). In particular, Foss demonstrated that detection ofa phoneme was facilitated in related versus neutral sentence contexts, but this difference was eliminated when the contexts were scrambled, even though the scrambled related context contained two associates preceding the targets and the adjacency of the associates and targets was maintained.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have analysed both semantic (e.g., Duffy, Henderson, & Morris, 1989;O'Seaghdha, 1989O'Seaghdha, , 1997Simpson, Peterson, Casteel, & Burgess, 1989;Williams, 1988) and syntactic (e.g., West & Stanovich, 1986) level context effects, generally concluding that syntactic primes lead mainly to inhibition but no facilitation, because they affect processes that occur after word access, whereas semantic priming is mainly facilitative, caused by lexical level word associations-e.g., dog primes cat, because they are associated words in the lexicon or co-occur frequently in the language (see Lucas, 1999;O'Seaghdha, 1997). In agreement with these studies, gender priming that leads to inhibitory syntactic effects has been reported in Italian using auditory gender monitoring (also called gender classification; Bates et al, 1996) and in German using visual lexical decision (Friederici & Schriefers, 1994;Schriefers, Friederici, & Rose, 1998) and cross-modal visual word naming (Friederici, Garrett, & Jacobsen, 1999 for an overview of the effects of gender in comprehension and production tasks; Jacobsen, 1999; see Schriefers & Jescheniak, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Simpson et al (1989) demonstrated that sentence effects in a word-naming task were not simply a result of activation of the sentence structure, but ofthe sentence meaning. In the present study, the fact that sentences were processed primarily when they included task-relevant words suggests that it was the meaning and not simply the structure of the sentences that received processing.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, lexical decisions are made more quickly when target words are preceded by semantically related primes (e.g., Sereno, 1991). Further, word recognition is enhanced when words occur in the context of meaningful phrases (e.g., O'Seaghdha, 1989) or sentences (e.g., Hess, Foss, & Carroll, 1995;Masson, 1986;Simpson, Peterson, Casteel, & Burgess, 1989).…”
mentioning
confidence: 99%